Incidence and predictors of intracranial bleeding after coronary artery bypass graft surgery - Kim, Ju Hyeon; Lee, Pil Hyung; Kim, Ho Jin; Kim, Joon Bum; Park, Sojeong; Kyoung, Dae-Sung; Kang, Soo-Jin; Lee, Seung-Whan; Kim, Young-Hak; Lee, Cheol Whan; Chung, Cheol Hyun; Lee, Jae Won; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background There is a paucity of direct data on the incidence and predictors of intracranial bleeding (ICB) after coronary artery bypass graft surgery (CABG). Methods The Korean National Health Insurance database was used to identify patients without prior ICB who underwent CABG. The outcomes of interest were the time-dependent incidence rates of ICB and the associated mortality. Results Among 35,021 patients who underwent CABG between 2007 and 2018, 895 (2.6%) experienced an ICB during a median follow-up of 6.0 years. The 1-year cumulative incidence of ICB was 0.76%, with a relatively high incidence rate (9.93 cases per 1,000 person-years) within the first 1–30 days. Subsequent incidence rates showed a sharp decline until 3 years, followed by a steady decrease up to 10 years. The 1-year mortality rate after ICB was 38.1%, with most deaths occurring within 30 days (23.6%). The predictors of ICB after CABG were age ≥ 75 years, hypertension, pre-existing dementia, history of ischemic stroke or transient ischemic attack, and end-stage renal disease. Conclusions In an unselected nationwide population undergoing CABG, the incidence of ICB was non-negligible and showed a relatively high incidence rate during the early postoperative period. Post-CABG ICB was associated with a high risk of premature death. Further research is needed to stratify high-risk patients and personalize therapeutic decisions for preventing ICB after CABG.